Silver nanoprism-based paper as a ratiometric sensor for extending biothiol detection in serum. (15th November 2017) - Ko, Yu-Chien; Lin, Tien-Li; Yeh, Chiu-Ting; Sun, Ning-Kuei; Shyue, Jing-Jong; Liu, Guang-Yang; Chou, Shang-Wei; Liu, Yu-Ci; Hsu, Chia-Hui; Ho, Mei-Lin
Abstract : A paper-based method with selectivity and a wider linear range for the detection ofl -Cys in serum using DTNB-modified Ag nanoprisms (AgP-DTNB ). Abstract : In this study, we present a selective paper-based method for the detection ofl -Cys in serum using DTNB-modified Ag nanoprisms (AgP-DTNB ). This method is based on the principle thatl -Cys reacts with DTNB inAgP-DTNB to release a TNB 2− chromophore and etches simultaneouslyAgP-DTNB to form Ag nanodisks, hence resulting in ratiometric changes of absorbance. Different biothiols have different affinities to etch the AgP surface and cause nanodisks of different sizes, which have slightly different resonance wavelengths. Thus, l -Cys can be discriminated with different biothiols on the basis of the different absorption spectral changes and different absorbance ratios. The linear dynamic range for the determination ofl -Cys was 1–1750 μM, and the correlation coefficient ( R 2 ) was 0.9968 ( y = 3.0859 × 10 −4 [Cys] + 0.9376). The limit of detection forl -Cys was calculated to be 0.87 μM from 3 times the standard deviation of the blanks to the slope of the calibration curve. Compared with the other nanoparticle-based sensors in solution and on paper, AgP-DTNB possesses a much wider linear range and a comparable detection limit forl -Cys. This paper-based sensor exhibits selectivity, a wide linear sensing range, low-volume sampling, miniaturization, portability, and disposability.